2017
DOI: 10.1111/pace.13179
|View full text |Cite
|
Sign up to set email alerts
|

The short‐term impact of the catheter ablation on noninvasive autonomic nervous system parameters in patients with paroxysmal atrial fibrillation

Abstract: This study demonstrated that the successful AFCA might concurrently impair the ANS parameters. The autonomic imbalance between the sympathetic and parasympathetic activity after AFCA could either become antiarrhythmic and/or proarrhythmic based on which of the two components was going to prevail after successful AFCA. The impaired ANS balance after PVAI might also be another hypothetical mechanism for AF recurrence particularly in the absence of PV reconnection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…In a prospective study, Kuyumcu, et al [19] documented an increase of RHR after cryoballon PVI for paroxysmal AF. No difference in the degree of RHR increase was noted in patients with and without recurrence in the 3-month follow-up period.…”
Section: Discussionmentioning
confidence: 97%
“…In a prospective study, Kuyumcu, et al [19] documented an increase of RHR after cryoballon PVI for paroxysmal AF. No difference in the degree of RHR increase was noted in patients with and without recurrence in the 3-month follow-up period.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, exercise performance [48] in patients with AF following catheter ablation has not been fully explored: On the one hand, in patients with longstanding asymptomatic persistent AF catheter ablation improved exercise performance [49]. On the other hand, HR recovery as well as chronotropic reserve has been found to be reduced in patients with paroxysmal AF for at least up to 3 months after PVI [50]. One might speculate that the latter is linked to reduced exercise performance even after successful restoration of sinus rhythm, especially considering our findings.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate the complexity and multiple functions of the CANS in inducing AF (29). A recent study also indicated that the autonomic imbalance between the sympathetic and parasympathetic tensions could be either pro-arrhythmic or anti-arrhythmic (30). In the present study, we utilized RVTS to successfully induce AF by reducing the ERP and increasing dERP, which was in agreement with published reports (31-34).…”
Section: Discussionmentioning
confidence: 99%